Embedment strength of dowels in wood specimens according to ABNT NBR 7190 (1997) and EUROCODE 5 (2004) - Molina, Julio Cesar; Cesar, Thacyane Katherine; Almeida, Carlino Carvalho De; Pallarolas, Ernesto Abel Fernando Friedmann (Fundação Gorceix, 2017)
Abstract The study of connections for timber structures has been the subject of intense research in Brazil. This work aimed to study the embedment strength of connections made by steel pins (dowels) in specimens of reforested woods. Analytical and experimental evaluations were considered in this study. Initially, tests on specimens made from Pinus elliottii (Class C30) and Eucalyptus salligna (Class C50) woods with dowels, type 1020, with diameter of 6.35 mm (1/4) were performed. The tests were performed according to the ANBT NBR 7190 (1997) and Eurocode 5 (2004) Standards with subsequent comparison between the analytical and experimental results for embedment strengths. The values of the embedment strength showed that the Eurocode 5 (2004) Standard had greater agreement between experimental and analytical results when compared to the results of the ABNT NBR 7190 (1997) Standard.
Keywords: embedment strength; analytical model; standardization; experimental tests